Molecular physiology and breeding at the crossroads of cold hardiness improvement - Castonguay Yves; Bertrand Annick; Cloutier Jean; Dube Marie-Pier; Laberge Serge; Michaud Real (Physiologia Plantarum, 2013)
Alfalfa (Medicago sativa L) is a major forage legume grown extensively worldwide with important agronomic and environmental attributes. Insufficient cold hardiness is a major impediment to its reliable production in northern climates. Improvement of freezing tolerance using conventional breeding approaches is slowed by the quantitative nature of inheritance and strong interactions with the environment. The development of gene-based markers would facilitate the identification of genotypes with superior stress tolerance. Successive cycles of recurrent selection were applied using an indoor screening method to develop populations with significantly higher tolerance to freezing (TF). Bulk segregant analysis of heterogeneous TF populations identified DNA variations that are progressively enriched in frequency in response to selection. Polymorphisms resulting from intragenic variations within a dehydrin gene were identified and could potentially lead to the development of robust selection tools. Our results illustrate the benefits of feedback interactions between germplasm development programs and molecular physiology for a deeper understanding of the molecular and genetic bases of cold hardiness.
Keywords: AFLP; Amplified fragment length polymorphism; BSA; Bulk segregant analysis; CBF; CNV; cold-regulated; Copy number variation; COR; c-repeat binding factor; c-repeat/dehydration responsive element; CRT/DRE; GBS; genotyping-by-sequencing; InDel; insertion and deletion; LD; linkage disequilibrium; marker-assisted selection; MAS; next-generation sequencing; NGS; QTL; quantitative trait loci; random amplified polymorphic DNA; RAPD; restriction fragment length polymorphism; RFLP; SCAR; sequence related amplified polymorphism; sequence-characterized amplified region; single-nucleotide polymorphism; SNP; SRAP; TF; tolerance to freezing